2016
DOI: 10.1155/2016/1326085
|View full text |Cite
|
Sign up to set email alerts
|

Helminthic Infection and Nutritional Studies among Orang Asli Children in Sekolah Kebangsaan Pos Legap, Perak

Abstract: Background. Orang Asli (aborigine) children are susceptible to soil-transmitted helminth (STH) infections due to their lifestyle and substandard sanitation system. Objectives. This study aimed to examine the helminthic and nutritional status of Orang Asli school children in Sekolah Kebangsaan Pos Legap, a remote primary school at Kuala Kangsar District in the state of Perak, Malaysia. In addition, the sensitivities of four STH stool examination techniques were also compared. Methods. Demography and anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…A total of 30 helminth-only [38,39,4144,47,48,5156,58,63,64,68,70,72,73,7679,8184] and 18 helminth-intestinal protozoa [47,53,86–92,95,97,101,102,110,112,113,116,119] studies provided categorical data concerning the number of parasites in each host and were evaluated using the Janovy model. Twenty studies demonstrated significantly different observed frequency distributions of infection compared to the frequency of host infection expected in each host class if infections were independent events for helminth-only studies, while ten studies demonstrated significant differences in these distributions for helminth-intestinal protozoa studies (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 30 helminth-only [38,39,4144,47,48,5156,58,63,64,68,70,72,73,7679,8184] and 18 helminth-intestinal protozoa [47,53,86–92,95,97,101,102,110,112,113,116,119] studies provided categorical data concerning the number of parasites in each host and were evaluated using the Janovy model. Twenty studies demonstrated significantly different observed frequency distributions of infection compared to the frequency of host infection expected in each host class if infections were independent events for helminth-only studies, while ten studies demonstrated significant differences in these distributions for helminth-intestinal protozoa studies (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…where z = 1.96; p = proportion of the population infected = 0.5 [10]; d = level of significance = 0.05. Assuming a non-response rate of 5%, the targeted sampling size was 384/ 0.05 = 404.…”
Section: Sampling Sizementioning
confidence: 99%
“…In Malaysia, geohelminthiasis is considered endemic, with the most common STH being Ascaris lumbricoides, Trichuris trichiura and hookworm [8]. Although the living standards of the Malaysian rural communities and indigenous people have been upgraded with better facilities through the government's efforts, high incidences of geohelminthiasis are still being reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] High intensity of STH infections in children showed negative impact on the nutritional status as infected children have decreased food intake, malabsorption, and poor food digestion. 7 The present study was done to determine the prevalence of various helminthes, the symptomatology and clinical manifestations of various helminthes and to correlate the nutritional status with the type of helminthic infestation.…”
mentioning
confidence: 99%